Role of the Perpetuation of Evidences and Claim Securrity in Litigation - Kazhashvili, Guliko (Journal of Law, 2017)
Perpetuation of evidences and securing of claim comprise two different institutes of procedural law. According to Civil Procedure Code, the court of the first instance shall directly examine the evidences. In USA the approach to the issue of perpetuation of evidences is different. Work provides practical approach to securing of claim - in which cases the court accepts the request of claim securing and in which cases it provides counter securing so that the adversarial and disposition principles were complied with.